Tourism Experience Quality and Agritourism Attractiveness Driving Tourist Loyalty: The Mediating Roles of Tourist Satisfaction and Perceived Value - Putu Eka Rini Larashati; Ni Luh Wayan Sayang Telagawathi; Ni Made Ary Widiastini (Institut Pariwisata dan Bisnis Internasional, 2026)
The transformation of modern tourism has shifted from attraction-based tourism toward experience-based tourism. However, previous studies have produced inconsistent findings regarding the mediating roles of tourist satisfaction and perceived value in explaining tourist loyalty, particularly within agritourism settings. This study aims to analyze the influence of tourism experience quality and agritourism attractiveness on tourist loyalty through tourist satisfaction and perceived value at grape-picking agritourism destinations in Buleleng Regency. An explanatory quantitative approach with a cross-sectional design was employed involving 120 tourists selected through purposive sampling. Data were analyzed using SEM-PLS. The findings reveal that tourism experience quality and agritourism attractiveness have a positive and significant effect on tourist satisfaction, perceived value, and tourist loyalty. Tourist satisfaction and perceived value were also confirmed as partial mediators in strengthening tourist loyalty.